Thinning trainer based on forest-growth model, virtual reality and computer-aided virtual environment. (February 2018) - Fabrika, Marek; Valent, Peter; Scheer, Ľubomír
Abstract: Immersive virtual reality is applied in many human activities. This virtual reality can be used as a training tool for thinning operations in forests. The aim of this study is to describe the complex solution of Thinning Trainer, that we developed. This system uses the SIBYLA growth model for predicting forest-growth development. The model, based on Virtual Reality Modeling Language, was chosen as a virtual reality environment. The CAVE Automatic Virtual Environment was implemented as a hardware tool for the Thinning Trainer, offering an immersive virtual reality of the forest for the users. Mutual connection of hardware, virtual reality and the SIBYLA growth model is established using a software solution called Caveman. Fully automatic system provides users with the possibility to interact and experiment with a virtual forest. Graphical abstract: Highlights: SIBYLA forest growth model is used to predict forest development. Simulated forest is produced as virtual reality. Interaction with a virtual forest is ensured with the CAVE system. Mutual connection is established by Caveman software. The Thinning Trainer is a unique product applicable in forestry science.